De novo ring chromosome 3: a new case with a mild phenotype. Issue 8 (August 1991) - McKinley, M; Colley, A; Sinclair, P; Donnai, D; Andrews, T
Abstract : We report an 18 year old female with a de novo ring chromosome 3 found after investigation for short stature. Her karyotype was interpreted as 46, XX, r(3)(p26.2q29). Her phenotype is milder than previously reported cases and illustrates the mild end of the spectrum of the ring chromosome 3 phenotype.